Implementation of Authentic Assessments in Daarul Qur’an International Primary School - Nety Ariyani; Syafrizal Syafrizal; Yudi Juniardi (English Department - University of Sultan Ageng Tirtayasa, 2024)
This study explores alternative assessment techniques in a grade six English class at Daarul Qur'an Primary School, Tangerang, with an emphasis on real-world applications and continuous improvement. While traditional assessments are still common, the introduction of Indonesia's 2024 Merdeka Curriculum highlights the need for more authentic assessments of language use. Using a descriptive qualitative method, data were gathered through observations, structured interviews, and document analysis. The study incorporates contextual teaching activities, such as video observations, email reading, role-playing, collaborative discussions, and group work, to enhance students' comprehension, pronunciation, vocabulary, and confidence in using English. These activities are designed to support the functional use of English in real-life scenarios. Formative assessments, including role plays, performance-based presentations, portfolios, and peer feedback, provide a comprehensive evaluation of students' progress. These methods foster active participation, creative thinking, and effective communication. The findings demonstrate that authentic assessments create a student-centered learning environment, promoting meaningful engagement and preparing students for practical communication challenges outside the classroom. By emphasizing real-world applications, these assessments lead to lasting learning outcomes and continuous improvement.